PENEGAKAN HUKUM LINGKUNGAN TERKAIT GALIAN C DI DESA SEBUDI KABUPATEN KARANGASEM - Tria Mantra; A A Ngr Gd Dirksen (Kertha Negara : Journal Ilmu Hukum, 2013)
Environment’s problems nowadays become hot issues among peoples, government orSocial Organizations that focus on environment. Many environment damages occurbecause of activities done by the peoples or they happen because of the influences of theenvironment itself. In the research writing entitled “The Maintenance of EnvironmentRules Related to Sand Quarying in Sebudi Village, Karangasem Regency, there are someproblems in quarrying area and how the efforts should be done if there are violations of arule in the quarrying activities. There are three efforts, administratif, civil and criminalsanctions. The method used in this research is Empirical Method. Finally, in SebudiVillage, there are many violations in the quarrying area that can damage the environmentin the future.